BLOW-UP OF SOLUTIONS FOR A VISCOELASTIC NONLINEAR KIRCHHOFF'S SYSTEM WITH DISSIPATIVE TERM - Quispe Méndez, Teófanes (2011)
In present work, we study the blow-up infinite time of solutions to the mixed problem relative to a system of viscoelastic nonlinear Kirchhoff's equatious with dissipative term.